2022
DOI: 10.1111/apt.17220
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal secretions reveal local food‐specific antibody responses in eosinophilic oesophagitis

Abstract: Background: Eosinophilic oesophagitis (EoE) is associated with elevated IgG4 in oesophageal tissue and serum. Previously, we showed brush-collected oesophageal secretions of EoE patients contained food antigen-specific antibodies IgA and IgG4. It is unknown whether other food-specific antibodies are present along the surface of the oesophagus in EoE. Aim: To identify whether immunoglobulins other than IgG4 and food-specific antibodies are elevated along the oesophageal mucosal surface in oesophageal secretions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recent randomized controlled trials have questioned the utility of peak eosinophil counts as a clinically meaningful endpoint in EoE [89,90]. In this regard, in two recent randomized controlled trials on novel biological drugs for EoE, namely the MESSINA (benralizumab) and KRYPTOS (lirentelimab) studies, most patients taking active treatment achieved histological remission, but the drugs failed to induce a significant improvement in symptoms compared to placebos [81,82]. In addition, a recent study comparing patients with symptomatic to patients with asymptomatic esophageal eosinophilia suggested that mast cells may contribute to the perception of symptoms in EoE, highlighting the possible role of other non-eosinophil-derived biomarkers in EoE [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent randomized controlled trials have questioned the utility of peak eosinophil counts as a clinically meaningful endpoint in EoE [89,90]. In this regard, in two recent randomized controlled trials on novel biological drugs for EoE, namely the MESSINA (benralizumab) and KRYPTOS (lirentelimab) studies, most patients taking active treatment achieved histological remission, but the drugs failed to induce a significant improvement in symptoms compared to placebos [81,82]. In addition, a recent study comparing patients with symptomatic to patients with asymptomatic esophageal eosinophilia suggested that mast cells may contribute to the perception of symptoms in EoE, highlighting the possible role of other non-eosinophil-derived biomarkers in EoE [52].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that EoE treatment may have an effect on mucosal IgG4s, as a significant decrease in esophageal IgG4s has been observed following the successful treatment of EoE [54]. More recently, Pyne et al [81] showed that patients with active EoE had elevated IgG2, IgG4, and IgM in esophageal luminal secretions compared to those with inactive EoE. In addition, the authors also found that food-specific IgG1, IgG2, IgG4, and IgM were significantly increased in patients with active EoE compared to EoE in remission.…”
Section: Other Non-eosinophil-derived Biomarkers In Eoementioning
confidence: 99%
“…Increased levels of milk and wheat sIgG4 have been found in the esophageal secretions from active EoE. 31,47 Preferential uptake of milk antigens was seen in the adult EoE mucosa, whereas gliadin penetration was more critically dependent on barrier perturbation and disease activity. 48 Thus, IgG4 production in response to distinct milk or wheat components may follow diverging trajectories and associate with distinct clinical phenotypes, as shown in IgE-dependent conditions.…”
Section: Discussionmentioning
confidence: 99%